The Diagnostic Approach to Headache in Otorhinolaryngology: A Systematic Review (GAIMS Journal of Medical Sciences, 2026)
Headache is a broad term that encompasses various types of head and neck pain syndromes. It is a ubiquitous symptom that frequently prompts patient presentation to otorhinolaryngology (ENT) clinics. While most headaches are primary headache disorders, a significant proportion can be secondary to underlying pathologies within the head and neck, falling within the purview of ENT specialists. The challenge lies in differentiating benign primary headaches from potentially serious secondary causes. This systematic review aims to synthesize the current literature on the diagnostic approach to headaches in otorhinolaryngology, focusing on the essential elements of history taking, physical examination, specific ENT-related differential diagnoses, appropriate investigations, and the crucial role of red flag identification.